IMPLEMENTATION OF ENVIRONMENTAL LAW IN SUSTAINABLE NATURAL RESOURCE MANAGEMENT - Hasibuan, Imelda; Japri, Muhammad (Awang Long Law Review, 2024)
East Kalimantan Province is endowed with abundant natural resources, including tropical forests, coal, oil, and natural gas. However, excessive exploitation of these resources has led to significant environmental degradation, including deforestation, land degradation, and water pollution. This study aims to assess the implementation of environmental law in supporting sustainable natural resource management in East Kalimantan, focusing on the effectiveness of regulations such as Law No. 32 of 2009 on Environmental Protection and Management, and the Environmental Impact Assessment (AMDAL) mechanism. The findings reveal that, despite the adequacy of the regulatory framework, its implementation remains weak due to insufficient monitoring, poor inter-agency coordination, and lenient enforcement of sanctions. Quantitative data show that approximately 45% of mining companies do not fully comply with AMDAL recommendations, while environmental oversight is minimal, with a critically low number of inspectors. To enhance the effectiveness of environmental law enforcement, steps such as improving government coordination, ensuring transparency in AMDAL processes, educating the public, and strengthening oversight and penalties are necessary. These strategies are expected to foster more sustainable natural resource management in East Kalimantan and mitigate further environmental damage.